Konsep Corporeta Social Responsibility Pegadaian Syariah Dalam Membantu Kemaslahatan Umat Islam - Mujibno Mujibno; Muhammad Samsul Solihin Saleh (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2020)
Social inequalities often occur among people, differences in income, employment and the needs of each community are different factors that differentiate. Corporate social responsibility is one of the social responsibilities in giving a little or even a lot to improve the welfare of the surrounding community. The existence of Corporate social responsibility can have a positive impact on society and the environment. PT. Sharia pawnshops are present in the midst of Indonesian society with the slogan